(untitled) (Economics and region, 2024)
The purpose of the development is to present the organizational and legal aspects of public administration in the field of public procurement in the Republic of Bulgaria. A legal analysis of the national legislation and European directives and regulations on the awarding of public procurement for the period from 1997 to 2024 was carried out. The objects and subjects of public procurement were highlighted. The rules for announcing and the 13 procedures regulated in the Public Procurement Act of 2016 have been analyzed. The problems in their practical application have been pointed out. Such are the problems related to regulated procedures, which are carried out with negotiation without prior announcement, negotiation without prior invitation to participate and negotiation without publication of a contract notice, as well as direct negotiation. Emphasis is placed on the positive effect of the complete electronicization of the procedures, through the use from the beginning of 2023 of a unified national electronic web-based platform. The problem of training contracting authorities and participants in public procurement to work with the new electronic platform has been highlighted. The role and specific functions of the Public Procurement Agency established by law, as well as the purpose of the public Register of Public Procurement, which it administers, has been analysed. The functions of the Minister of Economy, who implements state policy in the Republic of Bulgaria in the field of public procurement after 2014, are presented. The functions of the state bodies that carry out external, preliminary, current and subsequent control of appeals and contesting decisions in connection with the procedures for awarding public procurement are analyzed - Public Procurement Agency, State Financial Inspection Agency, Consumer Protection Commission, others authorized bodies, the Audit Chamber, the Supreme Administrative Court. An attempt has been made to defend the main thesis that the current regulatory framework gives rise to organizational and legal problems leading to corrupt practices and it is expedient to improve it.